Where will the baby sleep? attitudes and practices of new and experienced parents regarding cosleeping with their newborn infants. - Ball, Helen L. (American Antropological Association, 1999)
An evolutionary perspective on human infant sleep physiology suggests that parent-infant cosleeping, practiced under safe conditions, might be beneficial to both mothers and infants. However, cosleeping is not part of mainstream parenting ideology in the United States or the United Kingdom, and little evidence is available to indicate whether, and under what circumstances, parents sleep with their newborn infants. We present data from an anthropological investigation into the practices and attitudes of new and experienced parents of newborn infants regarding parent-infant sleeping arrangements in a community in the northeast of England. Despite not having contemplated cosleeping prior to the birth, new parents in our sample found it to be a convenient nighttime caregiving strategy, and one which was practiced regularly. Infants slept with both their parents, some being habitual all-night cosleepers, but commonly beginning the night in a cnb and sleeping with their parents for several hours following the early morning feed